Determinan Gagal Bayar Peer-to-Peer Lending Bukti Empiris dari Jawa Barat dengan Pendekatan ARDL - Meysa Mariela Faradyas Zahra; Ladi Wajuba Perdini Fisabilillah (Jurnal Ekonomika : INDEPENDEN, 2026)
This study aims to analyze the determinants of peer-to-peer (P2P) lending default in West Java Province using outstanding loan, number of borrowers, unemployment rate, and inflation as explanatory variables. The study employs the Autoregressive Distributed Lag (ARDL) approach to examine both short-run and long-run relationships among the variables. The results indicate that in the long run, outstanding loans, unemployment, and inflation have a positive and significant effect on default, while the number of borrowers has a negative and significant effect. In the short run, the dynamics of default show a pattern that is relatively consistent with the long-run relationship. These findings suggest that the default risk of P2P lending is influenced by a combination of credit expansion and regional macroeconomic conditions. Therefore, strengthening risk management and enhancing supervision over loan growth are essential to maintain the stability of digital financing.